2017
DOI: 10.1007/s10068-017-0160-9
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antibacterial activities of bioactive peptides in buffalo’s yoghurt fermented with different starter cultures

Abstract: The effect of 20552 ATCC (T2) or CH 5 (T3) in combination with yoghurt starter (1:1) on the antioxidant and antibacterial activities of the bioactive peptides present in buffalo's yoghurt was studied. The SDS-PAGE results indicate that all caseins were completely hydrolyzed by both strains, whereas whey protein fractions were still present. All starter cultures have the ability to produce low-molecular-weight bioactive peptides, most of which were originated from β-casein and fewer from αs casein. The antioxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 32 publications
(34 reference statements)
1
23
0
Order By: Relevance
“…Following fermentation, the water soluble extract (WSE) containing peptides can be readily separated by centrifugation ( Ayyash et al, 2017 ). This approach is used preferentially because it does not require the use of chemical agents ( Solanki et al, 2017 ; Taha et al, 2017 ).…”
Section: Methods For Baps Production By Lactobacillus mentioning
confidence: 99%
“…Following fermentation, the water soluble extract (WSE) containing peptides can be readily separated by centrifugation ( Ayyash et al, 2017 ). This approach is used preferentially because it does not require the use of chemical agents ( Solanki et al, 2017 ; Taha et al, 2017 ).…”
Section: Methods For Baps Production By Lactobacillus mentioning
confidence: 99%
“…The octapeptide SKVLPVPQ, isolated and identified in two commercial Spanish fermented milks produced with L. helveticus and S. cerevisiae, exhibited antioxidant activities [128]. A peptide composed of nine amino acids KIHPFAQTQ isolated from β-casein of buffalo's yogurt has proven to be particularly effective in antioxidant effects [129]. A total of 187 BPs derived from β-casein, αS1-casein, and αS2-casein were detected in cheeses by Pisanu et al [130].…”
Section: Antioxidant Peptides Identified In Commercial Fermented Dairmentioning
confidence: 99%
“…Studies have shown that buffalo milk peptide can improve antioxidant capacity in D-gal model aging mice [49]. Bioactive peptides in fermented buffalo yogurt display increased antioxidant activity [50]. In addition, some β-casein neuropeptides (LHLPLPL, β-CN f148-154) in gastrointestinal digest of dairy function as prolyl oligo peptidase (POP) inhibitors.…”
Section: Discussionmentioning
confidence: 99%